Vascular access in Senegalese patients starting chronic haemodialysis - Faye, Moustapha; Raqui, Ismail; Faye, Maria; Ba, Bacary; Lemrabott, Ahmed Tall; Seck, Sidy Mohamed; Niang, Abdou; Ka, Elhadji Fary (African Journal of Nephrology, 2023)
Introduction: It is recommended that patients should start chronic haemodialysis using an arteriovenous fistula (AVF). We aimed to determine the proportion of Senegalese patients who used an AVF at the start of haemodialysis and examined the factors associated with its use. Methods: We conducted a cross-sectional study from 1 June 2021 to 2 October 2021 among patients on chronic haemodialysis in 10 centres in the Dakar and Thiès regions. Clinical and laboratory data were collected from medical records and also via patient interviews. Results: The patients (n = 543) had a median age of 50 years [interquartile range (IQR) 40–62 years] and 50.6% were male. The socio-economic level was low in two-thirds of cases. The median duration of haemodialysis was 40 (IQR 17–76) months. Hypertension was noted in 92% and diabetes in 13%. Hypertensive kidney disease was the cause of kidney failure in 33%. Only 47 patients (9%) had started dialysis using an arteriovenous fistula. Factors associated with its use at haemodialysis initiation were socio-economic level (OR 0.48; 95% confidence interval (CI) 0.25–0.94 for low socio-economic level) and duration of pre-dialysis follow-up by a nephrologist for >4 months (OR 7.82; 95% CI 3.05–26.50). In 65% of prevalent patients, the vascular access used was an AVF, a tunnelled central venous catheter in 28%, an arteriovenous graft in 2% and a temporary central venous catheter in 4.4%. Conclusions: The proportion of Senegalese patients with an AVF at the start of haemodialysis was low. AVF use was associated with socio-economic level and pre-dialysis follow-up by a nephrologist for >4 months.